Alternative Land Dispute Resolution Outside the Court Through Mediation - Iwan, Irwan (SEAN Institute, 2025)
Land disputes are issues that always arise and are always relevant from time to time. Basically, land dispute resolution can be done in two ways, the most commonly used is dispute resolution through the courts and out of court through mediation. The process of dispute resolution through mediation is not something new in the cultural values of the nation, because the soul and nature of Indonesian society are known for their familial and cooperative nature in solving problems. In civil cases, dispute resolution through mediation has the highest legal force as long as it is carried out together and does not violate the provisions of applicable laws. The purpose of this study is to determine the advantages of alternative land dispute resolution outside the courts through mediation. The research method used is normative research using primary and secondary legal materials. Legal materials are obtained through literature studies such as books, journals, legislation and other documents related to the research. The results of the study explain that most Indonesian people feel that land dispute resolution through mediation can be implemented quickly because it does not rob or suppress individual freedom and delivers values of togetherness (community).